The Natural Flavonoid Galangin Elicits Apoptosis, Pyroptosis, and Autophagy in Glioblastoma - Kong, Yang; Feng, Zichao; Chen, Anjing; Qi, Qichao; Han, Mingzhi; Wang, Shuai; Zhang, Yulin; Zhang, Xin; Yang, Ning; Wang, Jiwei; Huang, Bin; Zhang, Qing; et al. (Frontiers in Oncology, 2019)
Galangin (GG), a flavonoid, elicits a potent antitumor activity in diverse cancers. Here, we evaluated the efficacy of GG in the treatment of human glioblastoma multiforme (GBM) and investigated the molecular basis for its inhibitory effects in the disease. GG inhibited viability and proliferation of GBM cells (U251, U87MG and A172) in a dose-dependent manner (IC50 =221.8, 262.5, 273.9 µM, respectively; P < 0.001; EdU, ~ 40% decrease at 150 µM, P < 0.001), and the number of colonies formed was significantly reduced (at 50 µM, P < 0.001). However, normal human astrocytes were more resistant to its cytotoxic effects (IC50 >450 µM). Annexin-V/PI staining was increased indicating that GG induced apoptosis in GBM cells (26.67% and 30.42%, U87MG and U251, respectively) and associated proteins including BAX and cleaved PARP-1 were increased (~ 3×). Cells also underwent pyroptosis as determined under phase-contrast microscopy. Knockdown of gasdermin E (GSDME), a protein involved in pyroptosis, alleviated pyroptosis induced by GG through aggravating nuclear DNA damage in GBM cells. Meanwhile, fluorescent GFP-RFP- MAP1LC3B puncta associated with autophagy increased under GG treatment, and transmission electron microscopy confirmed the formation of autophagic vesicles. Inhibition of autophagy enhanced GG-induced apoptosis and pyroptosis in GBM cells. Finally, in an orthotopic xenograft model in nude mice derived from U87MG cells, treatment with GG in combination with an inhibitor of autophagy, chloroquine, suppressed tumor growth and enhanced survival compared to GG monotherapy (P < 0.05). Our results demonstrated that GG simultaneously induces apoptosis, pytoptosis, and protective autophagy in GBM cells, indicating that combination treatment of GG with autophagy inhibitors may be an effective therapeutic strategy for GBM.